Gender and the heat pump transition - Jenny Crawley; Faye Wade; Mandy de Wilde (Buildings & Cities, 2023)
Decarbonisation in moderate and cold climates is reliant on the replacement of existing heating technologies with electric heat pumps. Heat pumps work differently from incumbent technologies, including in how they are controlled, their distribution of heat around the home and their space requirements. Despite evidence that domestic practices and interests associated with women played an important role in previous heating transitions, policy and research have not yet considered how heat pumps might interact with traditionally gendered needs and concerns. This could have significant implications for the success of the heat pump transition. This synthesis uses a framework of evidenced heating needs, incorporating wellbeing, resources, ease of use and relational dynamics, to structure a narrative literature review on how experiences of heat pumps may be gendered. Indicative evidence suggests that heat pumps have the potential to improve female thermal comfort, but that other possibly gendered heating needs such as minimising perceived waste and easy controllability are not always addressed. Amidst a lack of empirical studies exploring women’s needs, and whether they are met by heat pumps, a series of recommendations is provided for multidisciplinary research on the topic and to enhance consideration of gendered needs and experiences in policy development. Policy relevance Ensuring that heat pumps, and strategies designed to promote them, cater to diverse preferences and needs could support the current energy transition. This paper specifically considers experiences and practices traditionally understood as women’s priorities. Despite these playing a key role in previous heating transitions, current policy and industry strategies designed to support the heat pump transition have not yet taken gender into account. In addition, this article demonstrates that how traditionally female practices and experiences mingle with the use of heat pumps has not been taken into account in research, and that empirical evidence on this is currently limited. Consequently, policymakers urgently need to support a strengthening of the evidence base on gendered aspects of heat pump adoption and use. Against such evidence, heat policy can more fully consider and engage women, ultimately contributing to the success of the heat pump transition.